Brain tumor imaging - Jain, Rajan; Essig, Marco (Thieme, 2016)
Brain Tumor Imaging is a practical, comprehensive reference that covers all the methods of imaging used in the diagnosis and assessment of brain tumors. It includes key information on the use of advanced imaging technologies in the clinical setting for the successful treatment of patients with brain tumors